THE EU IN CENTRAL ASIA: TRATEGY IN THE CONTEXT OF EURASIAN GEOPOLITICS - KASSENOVA, Nargis (CENTRAL ASIA AND THE CAUCASUS, 2007)
The European Union is slowly but surely becoming an entity able to pursue a coordinated foreign policy. Every geopolitical ac-tor needs a strategy that can be applied both to all other big actors (the U.S., Russia, and China) and to the regions affecting Europe’s security and prosperity (Central Asia is one of them). The Central Asian region is unique in the fact that it is “impacted” between the EU’s largest and most important neighbor (Russia) and an emerging mega power (China).1 This means that the EU’s regional policy is strongly affected by its relations with both powers. Here I intend to assess the EU’s political prospects in Central Asia in the context of the relations among the European Union, Russia, and China.